2018
DOI: 10.1080/0142159x.2018.1460657
|View full text |Cite
|
Sign up to set email alerts
|

Can communication skills training improve empathy? A six-year longitudinal study of medical students in Japan

Abstract: Targeted educational programs to enhance empathy in medical students can have a significant effect; however, additional reinforcements may be needed for a sustained effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
84
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(94 citation statements)
references
References 30 publications
6
84
1
3
Order By: Relevance
“…However, whether empathy is sustained or enhanced long-term is not able to be determined. Indeed, a recent study suggests the need for repeated exposure to empathy-enhancing activities in order to reinforce the cognitive dimensions of empathic communication with patients continuously (Kataoka et al 2019). Further, students' learning in the affective domain could not be fully elucidated from the brief responses analyzed in the current study.…”
Section: Discussionmentioning
confidence: 75%
“…However, whether empathy is sustained or enhanced long-term is not able to be determined. Indeed, a recent study suggests the need for repeated exposure to empathy-enhancing activities in order to reinforce the cognitive dimensions of empathic communication with patients continuously (Kataoka et al 2019). Further, students' learning in the affective domain could not be fully elucidated from the brief responses analyzed in the current study.…”
Section: Discussionmentioning
confidence: 75%
“…Moreover, some studies that showed an increase in dental students' empathy noted this could be due to recently-completed communication lectures and practices [20]. Training in communication skills, including role playing with SPs who provide feedback, is effective in increasing empathy, but the effect is not sustained [21]. Although we provided medical interviewing training immediately after their enrollment, speci c communication instruction focused on empathy was not implemented during their residency in the present study.…”
Section: Discussionmentioning
confidence: 81%
“…Most previous studies have used a single measurement for empathy, especially self-reported measures [12,13,[15][16][17][18][19][20][21]. This may provide a limited understanding of empathy, because it is a multidimensional attribute.…”
mentioning
confidence: 99%
“…Moreover, some studies that showed an increase in dental students' empathy and noted that this could be due to recently completed communication lectures and practices [35]. Training in communication skills, including role playing with simulated patients who provide feedback, is effective in increasing empathy, but the effect is not sustained [36]. Although we provided medical interviewing training immediately after their enrollment, speci c communication instruction focused on empathy was not implemented during their residency in the present study.…”
Section: Discussionmentioning
confidence: 86%